Penerapan Community Based Tourism Di Kampung Lakkang Sebagai Daya Tarik Wisata - Hasrullah, Hasrullah; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p20, 2018)
This study aims to identify potential that could be being developed as a tourist attraction in Kampung Lakkang. Know the community perspective about the development of tourism. Know the development of tourism in kampung lakkang as tourist attraction and formulate the direction of the development based on the community based tourism aspects. Data collection techniques in this research is a technique observation, non-structural interview, and documentary method. Data analysis being used was thematic basis analysis. The results concluded that Kampung lakkang having many of tourism potential which rests in that the atmosphere rural and cultural nature. And the community viewed it is very appropriate to being developed as a tourist attraction thought as the currently of it’s development was very minimal. This case as caused with the limitation of the community knowledge of tourism, the lack of the community in exploiting the potential as attraction. Paradigma of the community who want to get the results are instant annd the lack of support and grant from the stakeholders, in this case private sector and government.  A conclusion of the development direction in kampung lakkang based upon the root issues concerning as community based tourism with provide provisions for the local community to develop Kampung lakkang, maximize performance disparekraf of makassar by making policy relates to the development of tourism facilities and infrastructure in Kampung lakkang and in partnership with the private stakeholders to supervising the community to increase creativity by making use of the community in creating business have been potential fields that is. Keywords: Tourism Potential, Community Perspective,  Community Based Tourism